Impact of hospital educational environment and occupational stress on burnout among Greek medical residents - Tsounis, Andreas; Malliarou, Maria; Sergentanis, Theodoros; Papaefstathiou, Efstathios; Papaefstathiou, Eirini; Sarafis, Pavlos (My University, 2019)
A number of risk and protective factors have been described on the development of burnout syndrome amongst medical residents. The current study aims to investigate the impact of hospital educational environment and occupational stress on trainee doctors burnout. A cross-sectional study among 269 medical residents was conducted. Greek version of Postgraduate Hospital Educational Environment Measure (PHEEM-G) for the assessment of their educational environment, Greek Version of Job Stress Measure (JSM-G) for the stress assessment and Copenhagen Burnout Inventory (CBI) for burnout measurement were used. RESULTS: Medical residents' perceptions about their educational environment are rather negative. Their job-related stress ranged between moderate and high levels, while burnout ranged in medium levels. A significant positive association was observed between total CBI and its subscales and stress. Positive evaluation of the clinical learning environment was inversely related with burnout levels. Job stress was correlated independently and positively with higher total burnout levels and its' three dimensions. Work-related burnout was independently and negatively related with social support.
Keywords: Burnout; Hospital; Quality of education; Residents; Stress